Cover Feature: Ion‐Pair SN2 Reaction of OH− and CH3Cl: Activation Strain Analyses of Counterion and Solvent Effects (Chem. Asian J. 9/2018). Issue 9 (17th April 2018) - Laloo, Jalal Z. A.; Rhyman, Lydia; Larrañaga, Olatz; Ramasami, Ponnadurai; Bickelhaupt, F. Matthias; de Cózar, Abel
Abstract : Back and forth : OH − is less prone than F − to react via frontside SN 2. It possesses a reactive cone of approach for barrierless substitution at CH3 Cl via the backside pathway in the gas phase. Solvation in THF further enhances this preference for backside over frontside SN 2 reaction. Yet, OH – can be pushed back to frontside substitution in the ion‐pair SN 2 reaction of MOH+CH3 Cl for M + =MgCl + . Herein, the physical principles behind this behavior based on quantum chemical activation strain analyses are unveiled. More information can be found in the Full Paper by Ponnadurai Ramasami, F. Matthias Bickelhaupt, Abel de Cózar et al. onpage 1138 in Issue 9, 2018 (DOI:10.1002/asia.201800082 ).